Comparison of the Effect of Two Variable Intraoperative Ventilation Modes on Pulmonary Compliance and Gas Exchange in Patients Undergoing Laparoscopic Abdominal Surgery - Ahmed, Mohamed Gaber; Mohamed , Ghada Adel; Gad, Gad Sayed; M.A. Ismail , Mahmoud (Journal of Neonatal Surgery, 2025)
Background: Pulmonary atelectasis is a common complication post-laparoscopic surgery due to carbon dioxide insufflation, which reduces lung compliance. Volume-controlled ventilation (VCV) is standard but increases airway pressures. Pressure-controlled volume-guaranteed ventilation (PCV-VG) may reduce stress but its benefits over VCV are debated. Aim: To compare VCV and PCV-VG regarding pulmonary compliance and gas exchange throughout laparoscopic abdominal surgery. Methods: A randomized controlled trial of 60 adult cases having elective laparoscopic surgery. Patients have been separated into two groups (30 each): VCV and PCV-VG. Outcomes measured included respiratory compliance, peak pressure, heart rate, mean arterial pressure (MAP), SpO₂, and adverse events. Results: The study included 60 participants (mean age 40.27±11.48 years, 1kg/m²). Surgery duration was 2.82±0.32 hours. Group B (PCV-VG) showed better SpO₂ and PaO₂, while Group A (VCV) had higher tidal volumes, peak pressures, and lower respiratory compliance. Respiratory compliance was significantly better in Group B (p<0.0001). Conclusion: PCV-VG outperformed VCV in pulmonary mechanics and gas exchange, with better oxygenation, lower peak pressures, and improved respiratory compliance. VCV was associated with higher airway pressures, increasing risks of barotrauma and atelectasis.